CHEMICAL COMPOSITION OF CARAPACE FLOUR OF VANNAME SHRIMP (Litopenaeus vannamei) - Dini Fitri; Rahman Karnila; Mirna Ilza (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT This research aimed to determine the chemical composition of vanname shrimp carapace flour. The measured parameters were proximate analysis consisting of (moisture, ash , protein and fat). This research method consisted of two stages : 1) preparation of making vanname shrimp carapace flour (Litopeaeus vanname), 2) analysis of proximate levels in vanname shrimp carapace flour (Litopeaeus vanname). The results of this research indicated that analysis of the proximate levels contained in vanname shrimp carapace flour (Litopeaeus vanname) was 10.53% of moisture content (wb). 33.28% of ash content (db) 37.44% of protein content. 1.80% fat content (db) and 27.52% of carbohydrates by difference (db). Keywords: Proximate levels, vanname shrimp carapace, preparation and flour